2020
DOI: 10.3390/ijerph17010368
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Women Prone to Restless Legs Syndrome?

Abstract: Restless legs syndrome is a relatively common neurologic disorder considerably more prevalent in women than in men. It is characterized by an inactivity-induced, mostly nocturnal, uncomfortable sensation in the legs and an urge to move them to make the disagreeable sensation disappear. Some known genes contribute to this disorder and the same genes contribute to an overlapping condition—periodic leg movements that occur during sleep and result in insomnia. Dopamine and glutamate transmission in the central ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 60 publications
1
19
0
2
Order By: Relevance
“…It has been reported that women are more prone to RLS, with it occurring about twice as frequently for women as for men in adults aged > 35 years (Allen et al., 2014; Manconi et al., 2012; Seeman, 2020). The underlying pathophysiology of preponderance of women in RLS remains unclear (Manconi et al., 2012; Seeman, 2020). Sex differences in human brain morphology have been consistently reported (Ruigrok et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that women are more prone to RLS, with it occurring about twice as frequently for women as for men in adults aged > 35 years (Allen et al., 2014; Manconi et al., 2012; Seeman, 2020). The underlying pathophysiology of preponderance of women in RLS remains unclear (Manconi et al., 2012; Seeman, 2020). Sex differences in human brain morphology have been consistently reported (Ruigrok et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, more female patients answered the survey. In general, women are also more prone to RLS than men [ 35 ]. In addition, regional differences in the prevalence of RLS exist.…”
Section: Discussionmentioning
confidence: 99%
“…Restless legs syndrome (RLS) or Willis-Ekbom disease is a motor-sensory disorder of the lower limbs associated with increased likelihood of sleep-wake disorders, such as poor sleep, poor daytime function and excessive daytime sleepiness in pregnancy. This condition is almost twice as common in women as in men, but reasons for this imbalance in prevalence are not precisely understood [76]. Indeed, the first known epidemiological study of RLS during pregnancy reported a prevalence of 11.3%, but in the third trimester prevalence appeared to rise up to 30%.…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…Other pharmacological agents, such as clonazepam, clonidine, and opioids may be needed in severe conditions, despite there is a high risk of neonatal withdrawal with these drugs [9,18]. Non-pharmacological treatments that can be used in pregnant women with RLS are physical exercise and behavioural strategies, such as reduced caffeine intake [76].…”
Section: Treatmentmentioning
confidence: 99%